R PENGEMBANGAN POTENSI USAHA BAKSO DI DESA LEMBUAK KECAMATAN NARMADA: - - Yuli Astini; Baehaki Syakbani; I Made Suardana; Ni Nyoman Yuliati; Rusli Amrul; Endang Kartini; Imam Samudra; Dina Wijayanti (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in improving community welfare and creating employment opportunities. One MSME with significant development potential is Bakso Nurhalimah, located in Lembuak Village, Narmada District, West Lombok Regency. However, several challenges were identified in its business operations, including suboptimal business management, limited financial record-keeping practices, inadequate marketing strategies, and the need to improve product quality and consistency. This community service program aimed to enhance the capacity of the business owner through assistance in production management, business management, and marketing activities. The implementation methods included observation and problem identification, socialisation and counselling, production assistance, business management assistance, marketing and promotion assistance, and evaluation. A participatory approach was employed by actively involving the business owner in every stage of the program. The materials delivered covered business management, simple financial bookkeeping, raw material inventory control, pricing strategies, product quality improvement, customer service, and the utilisation of social media as a marketing tool. The results indicated an improvement in the knowledge and skills of the business owner in managing the enterprise. The owner began implementing simple financial records, maintaining better product quality and hygiene standards, and utilising social media platforms such as WhatsApp, Facebook, and Instagram to support promotional activities. The assistance program also positively influenced the owner's awareness of the importance of structured business management and effective marketing strategies in enhancing business competitiveness. Based on the evaluation results, this community service program successfully contributed to improving the managerial capacity of Bakso Nurhalimah, thereby increasing its opportunities for sustainable business growth. Similar programs should be conducted continuously to support the development and strengthening of MSMEs as one of the main pillars of community economic development.